Correlation of Serum IL-6 Levels with Muscle Mass, Muscle Strength, and Physical Performance in Elderly Gymnastics Community in Mohammad Hoesin General Hospital Palembang - Muhammad Erfin; Nur Riviati; Nova Kurniati; Erial Bahar; Erwin Sukandi; Sudarto (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Introduction. Old age is related to geriatric syndrome where there are several health problems that often occur related to a decrease in body function and an increase in the inflammatory process. Decrease in muscle mass, muscle strength and physical performance will cause a condition of sarcopenia and frailty syndrome in the elderly. The importance of prevention so that sarcopenia does not occur in the elderly by evaluating the factors that can cause it, one of which is controlling interleukin 6 (IL-6) as proinflammatory. The purpose of this study was to determine the correlation between serum IL-6 levels with muscle mass, muscle strength and physical performance in the elderly gymnastics-community in Mohammad Hoesin General Hospital, Palembang. Methods. This research is an observational analytic study with a cross-sectional approach which was conducted at the Integrated Geriatric Clinic Internal Medicine RSMH Palembang from November 2019 to November 2020. A sample of 31 people aged > 60 years was examined for muscle mass, muscle strength, physical performance and IL-levels. 6 serum. All data processing and analysis in this study used the SPSS version 25 for Windows program. Results. of the 31 subjects, 27 were female (87.1%) and 4 male (12.9%). The mean value of muscle mass is37.9 kg/m2, muscle strength 23 kg, and physical performance 6.1 m/sec.There were 28 (90.3%) samples with elevated serum IL-6 levels, while 3 (9.7%) samples had normal levels. There was a significant negative correlation (p = 0.000) with a strong correlation strength (r = -0.722) between serum IL-6 levels and muscle mass and a significant negative correlation (p = 0.050) with a weak correlation strength (r = -0.354) between IL levels -6 serums with physical performance. Conclusions. There was a significant negative correlation between serum IL-6 levels and muscle mass and physical performance. So, it is very important to prevent an increase in serum IL-6 levels so that the elderly do not fall into a state of sarcopenia.